Study of adipokinetic hormone role in insects stressed by entomopathogenic nematodes - Ibrahim, Emad Ahmed Sayed (Jihočeská univerzita, 2019)
In this thesis, the effect of infection elicited by entomopathogenic nematodes (EPNs) Steinernema carpocapsae on Pyrrhocoris apterus and Drosophila melanogaster models were evaluated, and a role of adipokinetic hormones (AKHs) during the infection was characterized. These were monitored by determination of mortality, and various biochemical and physiological characteristics such as AKH levels both in the central nervous system (CNS) and in hemolymph, AKH gene expression in CNS, level of anti-oxidative stress markers, general metabolism and level of nutrients in normal and genetically modified insects. At P. apterus the mortality tests revealed that application of AKH increases the efficacy of EPN treatment. This result was confirmed using the firebugs with AKH receptor deficiency. Further, the increase of AKH expression and AKH levels in CNS and hemolymph seemed to be coordinated after the nematode treatment. At the D. melanogaster model also, the effect of adenosine into the above-mentioned characteristics was included. For this, mutants in AKH (AHK1), adenosine receptor (AdoR1) genes, and in both these genes together (AHK1 AdoR1 double mutant) were employed. Altogether, the results confirmed the involvement of AKH, and partially also adenosine into the antistress defense reactions elicited by the nematobacterial infection. Finally, the last part of the study was focused on examination of the vitellogenin (Vg) role in the defense reaction in firebug body P. apterus affected by two entomopathogenic organisms, the nematode S. carpocapsae and the fungus Isaria fumosorosea. The results revealed that Vg proteins play an important role in the defense against both types of the infections and are also able to kill entomopathogenic bacteria Xenorhabdus nematophila, that are symbionts of S. carpocapsae and that increase toxicity of this nematode.
Study of adipokinetic hormone role in insects stressed by entomopathogenic nematodes
Keywords: Mortality; Akh gene expression; AKH receptor; Metabolism; RNAi; Pyrrhocoris apterus; Adipokinetic hormone; Adenosine; Drosophila; Oxidative stress; Locomotion; insect; vitellogenin; infection; entomopathogenic nematode; entomopathogenic fungus; antimicrobial activity; Mortality; Akh gene expression; AKH receptor; Metabolism; RNAi; Pyrrhocoris apterus; Adipokinetic hormone; Adenosine; Drosophila; Oxidative stress; Locomotion; insect; vitellogenin; infection; entomopathogenic nematode; entomopathogenic fungus; antimicrobial activity